Research in virtual engineering - Hren, Gorazd (JET on-line, 2018)
Virtual reality systems and 3D printing have achieved an adequate level of development to be considered in innovative applications in education and research. One of the challenges of this technology is the associated costs, which have been unaffordable for educational and research institutes. However, in recent years, computer hardware and software accompanied by the development of printing technology has made it more feasible for teaching strategies. From the research point of view, it is time for companies to innovate by incorporating new technologies, particularly those that inject products with greater intelligence and the ability to monitor, learn, and fix problems while functioning in their virtual environment.
Keywords: 3D printing; 3D tiskanje; education; izobraževanje; prototipi; rapid prototyping; raziskovanje; research; virtual engineering; virtual reality abstract virtual; virtualno strojništvo